Evaluasi Plasma Nutfah Kacang Tunggak (Vigna unguiculata L.) di Lahan Masam - Mamik Setyowati; Sutoro Sutoro (Buletin Plasma Nutfah, 2010)
Plant genetic resources are as a source of geneticvariability and can be used to develop new varieties tolerant toabiotic and biotic stress. Evaluation of cowpea germplasm toabiotic stress, such as acidic soil has to be done to obtaininformation of their tolerance. Cowpea germplasm collectionheld in ICABIOGRAD was tested under acidic soil conditionin Jasinga, West Java and Bogor as control during March-June2007. The criteria of tolerance to acidic soil was determinedwhen the grain yield of cowpea under acidic soil more than80% compare to those yield under non acidic soil, whilesusceptible to acidic soil when lower than 25%. Result ofexperiment showed that accession of LO-3-38, Ces-41-6,TVX-4661-01D-A, IT82-889-A, TV.3381-0-2j-B and KacangTolo Loreng were tolerant to acidic soil, while Kacang Dadapdan Kacang Tolo were susceptible. These accessions could beused as parent materials for genetic study related to acidic soilstress.